DETERMINASI KUALITAS PENYAJIAN LAPORAN KEUANGAN DANA BOS SD DI KECAMATAN LAWEYAN - Setiawan, Rudita; Octavia, Dewi Ika (Komunitas Manajemen Kompetitif, 2025)
This study examines the factors that influence the quality of financial report presentation of the School Operational Assistance Fund (BOS) in elementary schools in Laweyan Sub-district. The focus of this research includes human resource competencies, accounting information systems, and internal control. By using a survey-based quantitative method through questionnaires, the results showed that HR competencies and internal control have a significant influence on the quality of financial statements, while the accounting information system did not show the same influence. These findings highlight the importance of improving HR competencies as well as strengthening internal control systems to achieve better transparency and accountability in BOS Fund financial reports.